Macroalgae Extracts From Antarctica Have Antimicrobial and Anticancer Potential - Martins, Rosiane M.; Nedel, Fernanda; Guimarães, Victoria B. S.; da Silva, Adriana F.; Colepicolo, Pio; de Pereira, Claudio M. P.; Lund, Rafael G. (Frontiers in Microbiology, 2018)
Background: Macroalgae are sources of bioactive compounds due to the large number of secondary metabolites they synthesize. Antarctica is characterized by extreme weather conditions and abundant aggregations of macroalgae; however, current knowledge about their biodiversity and their potential for bioprospecting is still unclear. This study aimed to evaluate the antimicrobial and cytotoxic activity of different extracts of four macroalgae (Cystosphaera jacquinotii, Iridaea cordata, Himantothallus grandifolius and Pyropia endiviifolia) from the Antarctic against cancer and non-cancer cell lines. Methods: Their antimicrobial activity was evaluated by the broth microdilution method. The extracts were assessed against Staphylococcus aureus ATCC 19095, Enterococcus faecalis ATCC 4083, Escherichia coli ATCC29214, Pseudomonas aeruginosa ATCC 9027, Candida albicans ATCC 62342 and the following clinical isolates from the human oral cavity: C. albicans (3), C. parapsilosis, C. glabrata, C. lipolytica and C. famata. Cytotoxicity against human epidermoid carcinoma (A-431) and mouse embryonic fibroblast (NIH/3T3) cell lines was evaluated with the MTT colorimetric assay. Results: An ethyl acetate extract of H. grandifolius showed noticeable antifungal activity against all the fungal strains tested, including fluconazole-resistant samples. A cytotoxicity investigation using a cancer cell line revealed that an ethyl acetate extract of I. cordata was highly cytotoxic against the A-431 cancer cell line, increasing the inhibitory ratio to 91.1% and 95.6% after 24 and 48 h of exposure, respectively, to a concentration of 500 μg mL-1. Most of the algal extracts tested showed little or no cytotoxicity against fibroblasts. Conclusion: Our data suggest that macroalgae extracts from Antarctica may represent a source of therapeutic agents.